Comparison of Topical Anesthetics for Radiofrequency Ablation of Achrocordons: Eutectic Mixture of Lignocaine/Prilocaine versus Lidocaine/Tetracaine. (29th January 2014) - Gahalaut, Pratik; Mishra, Nitin; Chauhan, Sandhya; Rastogi, Madhur Kant
Abstract : Introduction . Topical application of local anesthetics is currently considered to be the easiest, most effective, and convenient way for treatment of patients who may be undergoing superficial dermatosurgical procedures. Materials and Methods . This study compares the anesthetic potential of 2.5% lidocaine and 2.5% prilocaine topical cream with 7% lignocaine and 7% tetracaine combination cream for radio ablative dermatosurgery when applied, under occlusion, for 30 minutes. 40 subjects of achrocordons were enrolled in this split-side randomized trial. Result . The pain severity experienced by subjects in terms of visual analogue scale score was significantly lesser for lignocaine/tetracaine combination cream as compared to lidocaine/prilocaine combination. Conclusion . This small study proves the efficacy of lidocaine/tetracaine combination as a topical anesthetic cream when applied for a short time interval of 30 minutes. This will help a dermatosurgeon to perform various dermatological procedures in a better and efficient manner with a shorter waiting period for analgesia to set in.